PECULIARITIES OF USING INTERACTIVE METHODS IN TEACHING "EDUCATION" IN PRIMARY EDUCATION (Academia Science Repository, 2023)
In this article, effective implementation of interactive methods in teaching the subject of "Education" to elementary school students and the standards of teacher's effectiveness, cooperative teaching, interactive methods are analyzed.